Juha Manninen and Friedrich Stadtler (eds.), The Vienna Circle and the Nordic Countries. Networks and Transformations of Logical Empiricism (Vienna: Vienna Circle Institute Yearbook vol.14, Springer, 2010) - Carlo Penco (Nordicum-Mediterraneum, 2013)
A discussion of The Vienna Circle and the Nordic Countries. Networks and Transformations of Logical Empiricism, edited by Juha Manninen and Friedrich Stadtler, Vienna Circle Institute Yearbook vol.14, Springer, 2010.